Studies in East Baltic consonant clusters 1: *šr - Jakob, Anthony (Baltistica, 2025)
This article focuses on the sources and outcome of the cluster *šr in East Baltic. This cluster is conspicuously absent in word-initial position. This appears to be the result of “Weise’s law”, which describes a phonotactic limitation against clusters of the type *Ḱr in Proto-Indo-European. In Balto-Slavic, there is also evidence that Weise’s law applied word-medially: where the cluster *-šr- does occur, there is usually a clear model for the restoration of *-š-. An interesting case is *ašra- ‘sharp’ — as the most basic member of the word family, and given exact parallels in other Indo-European languages, it is not likely the result of a recent restoration. This paper examines this lemma in detail. First, with the help of a parallel in strė́nos ‘small of the back’, it is shown that Lithuanian aštrùs ‘sharp’ must reflect a proto-form without *-t-. Second, it is argued that Latvian ass ‘sharp’ may also reflect Proto-East-Baltic *ašra- through a novel sound law *-šr- > -s-. Two probable and two more possible parallels can be found for this sound change. While the evidence as a whole supports the validity of Weise’s law in both word-initial and word-medial position, various evidence points towards the law having ceased to be productive in Proto-Indo-European, thus placing it in a pre-PIE timeframe.
Keywords: sound law; Proto-Indo-European; phonotactics; Weise’s law